DEVELOPMENT OF METHODS FOR IDENTIFICATION OF DESLORATADINE IN MEDICINES - Logoyda, Liliya (Здобутки клінічної і експериментальної медицини, 2015)
SUMMARY. Methods of identification of desloratadine in medicines by absorpt i on spectrophotometry and TLC have been developed. KEY WORDS: desloratadine, identification, spectrophotometery, thin layer chromatography, validation.